REVOLUTIONIZING THERAPEUTIC APPROACHES IN CHRONIC VENOUS INSUFFICIENCY: A LITERATURE REVIEW - Bartłomiej Czarnecki; Jan Nowak; Illia Koval; Bartosz Zwoliński; Kacper Sukiennicki; Wirginia Bertman; Natalia Kołdej; Zuzanna Kępczyńska; Wiktor Kubik; Katarzyna Szewczyk; Kamil Borysewicz; Klaudia Romejko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Chronic venous insufficiency (CVI) is a prevalent, progressive vascular disorder that burdens patient health and quality of life. Current treatments: compression therapy, pharmacological agents, and surgery vary in efficacy and are often linked to poor symptom control, recurrence, or side effects. Thus, there is a need for novel therapies that improve outcomes. Recent advances in pharmacotherapy and minimally invasive methods offer promising options for enhancing venous function and symptom relief. This study critically assesses the efficacy, safety, and clinical relevance of emerging pharmacological and interventional treatments for CVI. Material and methods: A comprehensive literature search was conducted in PubMed and Google Scholar using keywords: "chronic venous insufficiency", "venous disease", "novel treatment", "minimally invasive therapy", "pharmacological therapy". Selected studies were analyzed for therapeutic efficacy, safety, and clinical outcomes of proposed treatments. Aim of the study To evaluate the effectiveness, safety, quality of life, and potential clinical use of novel therapies for chronic venous insufficiency. Conclusion: Innovative drugs and minimally invasive procedures offer new alternatives for CVI, improving venous function and symptom relief. However, more high-quality clinical research is needed to confirm long-term safety, efficacy, and define optimal treatment protocols, enhancing care standards for venous disorders.